Validity and Reliability of the Student Refractive Error and Eyeglasses Questionnaire—Revised Version in Myopic Children. Issue 11 (13th November 2021) - Marupuru, Srujitha; Dahlmann-Noor, Annegret; Crescioni, Mabel; Slack, Marion; Barnard, Simon; Amerat, Imran; Loveday, Adam; Chauhan, Dharshana; Adler, Paul; Walker, Rosemary; Warholak, Terri L.
Abstract : SIGNIFICANCE: Multiple vision-related quality of life (VRQol) instruments exist, but questionnaires designed specifically for myopic children that are appropriate for assessing the impact of refractive error are rare. PURPOSE: This study aimed to assess the validity and reliability of the Student Refractive Error and Eyeglasses Questionnaire – Revised (SREEQ-R) in school-aged children with myopia in the United Kingdom. METHODS: Community optometrists in the United Kingdom invited children up to the age of 18 years presenting for an eye examination with current or previous reported use of eyeglasses for myopia to complete the SREEQ-R, which consists of 20 specific items divided into two sections each with three response categories. The "without glasses" section relates to perceptions of uncorrected vision/not wearing glasses, and the "with glasses" relates to corrected vision/wearing glasses. Rasch analysis was used to explore the psychometric performance (content, construct validity, and reliability) of the questionnaire items and scale using Winsteps software (Winsteps.com. Portland, OR). RESULTS: A total of 125 eligible children with a mean ± standard deviation age of 12.7 ± 2.9 years completed the SREEQ-R. All items fit the Rasch model and were retained, and the scale was found to be unidimensional. All children and item infit and outfit mean square statistics fell within the recommended fit criteria. As per the Rasch analysis, the person reliability coefficients were 0.84 and 0.91, whereas item reliabilities were 0.99 and 0.80 for the without glasses and with glasses sections, respectively. The internal consistency for the SREEQ-R was good; Cronbach α values were 0.84 for without glasses and 0.91 for with glasses. CONCLUSIONS: The SREEQ-R had satisfactory validity and reliability evidence. Construct validity of the scale was supported to measure the impact of uncorrected and corrected refractive error on vision-related quality of life in myopic school-aged children in the United Kingdom. The SREEQ-R could be used in future studies to evaluate vision-related quality of life in children with myopia.